2020
DOI: 10.21857/mnlqgc5vgy
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic proteins: From discovery to development of a novel autologous bone graft substitute consisting of recombinant human BMP6 delivered in autologous blood coagulum carrier

Abstract: Bone Morphogenetic Proteins (BMPs) are growth and differentiation factors within the TGFβ superfamily of proteins. They induce ectopic and orthotopic endochondral bone formation and are involved in the regulation of cell proliferation, differentiation, apoptosis and mesenchymal-epithelial interactions in critical morphogenetic processes of tissues beyond bone. BMP2 and BMP7 osteogenic devices have been approved for enhancing healing in patients with long bone defects and anterior spinal fusion procedures. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 108 publications
(190 reference statements)
0
6
0
Order By: Relevance
“…e following requirements are met with the introduction of Osteogrow, a novel therapeutic solution comprised of rhBMP6 delivered within autologous blood coagulum (142,143). To improve the biomechanical properties of Osteogrow implants might be supplemented with allograft bone (Osteogrow A), host bone (Osteogrow B) and synthetic ceramics (Osteogrow C) (144)(145)(146).…”
Section: Bmps In Regenerative Medicine and Clinical Developmentmentioning
confidence: 99%
“…e following requirements are met with the introduction of Osteogrow, a novel therapeutic solution comprised of rhBMP6 delivered within autologous blood coagulum (142,143). To improve the biomechanical properties of Osteogrow implants might be supplemented with allograft bone (Osteogrow A), host bone (Osteogrow B) and synthetic ceramics (Osteogrow C) (144)(145)(146).…”
Section: Bmps In Regenerative Medicine and Clinical Developmentmentioning
confidence: 99%
“…We have recently developed an autologous bone graft substitute (ABGS) comprised of BMP6 delivered within an autologous blood coagulum to which a compression-resistant matrix, such as allograft or synthetic ceramics, can be added [22,73,74,76,[86][87][88][89][90][91][92]. Moreover, the volume of newly induced bone increased with the elevation of the CRM amount, which might be attributed to the enlargement in an overall surface area [73].…”
Section: Bone Regeneration By Bone Morphogenetic Protein Devicesmentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs) are growth and differentiation factors known for their ability to induce cartilage and bone and have a morphogenic role in the development and maintenance of tissue structure throughout the body [1,2]. The ability of BMPs to induce bone was evaluated in various animal models used for the translation of the bone regeneration principle for clinical use [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that our novel autologous bone graft substitute (ABGS) containing rhBMP6 within autologous blood coagulum (ABC) with or without compression resistant matrix (CRM) restores large bone defects and achieves successful lumbar fusion in rabbits and sheep [2,[12][13][14][15][16][17][18][19]. Importantly, newly induced bone successfully fused with native bone, achieving complete osseointegration, which can be defined as functional fusion between new and old bone [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation